Bassalygo-Dobrushin uniqueness for continuous spin systems on irregular graphs - Kępa, D.; Kozitsky, Yu. (Condensed Matter Physics, 2008)
An extension of the Bassalygo-Dobrushin technique of proving uniqueness of Gibbs fields on irregular graphs,
developed in [Theory of Probab. Appl. 31, 572–589 (1986)], to the case of continuous spins has been presented. Подається розширення технiки Бассалиго-Добрушина для доведення єдиностi гiббсових полiв на нерегулярних графах для систем неперервних спiнiв.